Скорость полета и размеры птиц - Цвелых, А.Н. (Вестник зоологии, 1982)
Within homomorphic bird groups, differing in size, the flight velocity increases along with body mass up to the mass 200-300 g (in terns-proportionally t othe bodymass ni a power of 1/6, in Charadriiform -1/4). After approaching the"critical"mass, flight velocity stops increasing. This phenomenon depends on the fact, that in birds whose mass does not exceed the "critical" point, available capacity remarkably exceeds that required for flight. At further body size increase the power deficiency rises, which causes compensatory changes in a bird flight system, ie. a natural geometric conformity break, permitting the flight ability without a velocity increase.